Learning L2 collocations incidentally from reading - Pellicer-Sánchez, Ana (SAGE, 2015)
Previous studies have shown that intentional learning through explicit instruction is effective for the acquisition of collocations in a second language (L2) (e.g. Peters, 2014, 2015), but relatively little is known about the effectiveness of incidental approaches for the acquisition of L2 collocations. The present study examined the incidental acquisition of collocational knowledge when learners encounter adjective-pseudoword collocations while reading. Forty-one L2 learners read a story containing six target collocations in a classroom setting. One week after the reading they were interviewed about their knowledge of the form, meaning and collocation of the target items (at recall and recognition levels). Participants were randomly assigned to one of two experimental groups, i.e. the 4-repetition group and the 8-repetition group. Results showed that collocational knowledge can be learnt incidentally from reading; that it is learnt at a similar rate to other lexical components such as form and meaning of individual words; and that the frequency manipulation in this study did not seem to have a significant effect on the acquisition of any of the aspects examined.